If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + 5x = 10 + -8x Solving 20 + 5x = 10 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 20 + 5x + 8x = 10 + -8x + 8x Combine like terms: 5x + 8x = 13x 20 + 13x = 10 + -8x + 8x Combine like terms: -8x + 8x = 0 20 + 13x = 10 + 0 20 + 13x = 10 Add '-20' to each side of the equation. 20 + -20 + 13x = 10 + -20 Combine like terms: 20 + -20 = 0 0 + 13x = 10 + -20 13x = 10 + -20 Combine like terms: 10 + -20 = -10 13x = -10 Divide each side by '13'. x = -0.7692307692 Simplifying x = -0.7692307692
| 11.5=14t+20.6 | | 21x+3y=210 | | x^2=-192 | | 30x^3+26x^2+4x= | | x-1/3=12 | | 6x+3x=3x-x | | x/2-3-x≥1 | | 4/(-2-8i) | | 9a+10=64 | | 3x+4.8=12 | | 4(x-7)=6(x-9)+60 | | 1x+2y=60 | | N/24=4/9 | | 0.7xX=29820 | | 8-0.03w=1.8 | | 3(x+4)=x-3 | | 3v+13=40 | | M^2=-49 | | 20+-3(2x+-7)=5(x+5)+-6 | | 9x+4=4x+9 | | 5/18=6/x | | (3x^2+4x-3)=(4x^2-3x+2) | | 10-3(2x-7)=5(x+5)-6 | | -7(x+1)=13 | | y-4=4*(1+0) | | -2(x-4)=3x+6-1x | | 12=a/5-4 | | 13(x-1)=7x+23 | | 15x=18+13x | | 13y+36=153 | | 8(4s+9)=328 | | -3x-6/4=3 |